Implementasi Proses Asuhan Gizi Terstandar pada Pasien Diabetes Mellitus Tipe 2 dengan Pneumonia dan Post-COVID 19: Sebuah Laporan Kasus - Nuansa, Maria Khana; Sumarmi, Sri (Media Gizi Kesmas, 2024)
Background: Type 2 diabetes mellitus patients require special nutritional care to maintain blood sugar levels and meet nutritional needs. Especially in cases of type 2 diabetes mellitus with pneumonia and post-COVID 19 which affects the ability to consume food adequately. The B1 diet is a diet for diabetes sufferers who require a high protein intake. The standardized nutritional care process is carried out by providing B1 diet to lower blood sugar levels and reduce the risk of disease severity. Objectives: To determine the management of standardized nutritional care for type 2 diabetes mellitus patient with pneumonia and post-COVID 19 who use the B1 diabetes mellitus diet. Methods: A case study was conducted in February 2021 on a patient at RSUD Dr. Soetomo Surabaya. The data collection method was observation for 3 days on intake, physical/clinical, anthropometric and biochemical domains. Researchers also conducted literature studies to complete and analyze the data. Results: After nutritional intervention, the patient's physical/clinical complaints began to decrease, GDP levels gradually decreased, and the patient's intake gradually increased although it had not yet reached the target (<80%). Conclusion: Based on the results of monitoring and evaluation, the nutritional intervention provided had not reached the target, but the patient's condition is gradually improving.